(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article was based on research that sought to analyzes the relationship between poverty and performance. In this article, Brazilian production in Performing Arts was explored in the form of articles in high-impact journals to discuss the presence or absence of poverty and poor markers as a way of identifying the contexts in which research participants live. Thus, the neoliberal discourse about situations of poverty was problematized. It was concluded, finally, that the absence of such markers in the Brazilian production in Performing Arts constitutes a sort of ethics, a kind of care of the researches towards the participants, considering the dangers of discursive inscription of the categories poverty and poor with possible negative effects or embarrassing for the participants.